Localized morphea profunda: An atypical presentation - Dhabal, Arunima; Chandra, Ananya; Khan, Sumana; Barua, Jayanta Kumar (Indian Journal of Case Reports, 2020)
Morphea profunda is a variant of localized scleroderma, in which inflammation and sclerosis are found in the deep dermis, panniculus, fascia, or superficial muscle. It generally presents as diffuse, taut, and thickened skin, which is bound to the underlying tissue. Most cases have widespread involvement, but localized lesions have also been reported. We report a case of localized morphea profunda presenting with papular and vesiculobullous lesions on the overlying skin in a 50-year-old female patient who was successfully treated with methotrexate and systemic steroids.